copper parts
Patent Information
- Application Number
- CN202280008657.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-20
- Filing Date
- 2022-03-23
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-03-23
AI Technical Summary
现有的减成法和半加成法(SAP)法在布线微细化过程中难以满足微细化要求,尤其是铜膜厚度薄且与树脂基板的密着性不足,导致布线微细化和高频特性差。
By forming a copper oxide layer on the surface of the copper component and controlling the S/N ratio, metal composition ratio, and seed layer thickness on the surface of the copper component during hot pressing and peeling, combined with the use of silane coupling agents or rust inhibitors, an optimized copper component structure is formed.
It improves the adhesion between copper components and resin substrates and the formation of fine wiring, enhances high-frequency characteristics, and meets the requirements for wiring miniaturization.
Smart Images

Figure CN116670326B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a copper component. Background Technology
[0002] In recent years, the demand for miniaturized wiring has increased, and existing subtractive methods that use insulating resin with copper foil to etch away unwanted copper portions (Japanese Patent Application Laid-Open Nos. 2005-223226, 2010-267891, and 2002-176242) cannot meet the requirements for miniaturization. Therefore, wiring technologies such as semi-additive processing (SAP) and modified semi-additive processing (MSAP) have been developed. Compared to subtractive methods, MSAP etches a thinner copper film, thus enabling miniaturized wiring.
[0003] The MSAP routing technique involves using an extremely thin copper foil with a carrier, formed on a support with a copper layer several μm thick through a release layer. After forming a seed layer on an insulating resin, a thick electroplated copper layer is formed on the patterned area laminated with resist. Routing is then achieved by removing the resist and the seed layer (see [reference]). Figure 1A Compared to subtractive etching, the MSAP method etches a thinner copper film, thus enabling miniaturized wiring.
[0004] The SAP method typically involves forming a copper seed layer on a resin substrate. To ensure adhesion between the resin substrate and the seed layer, the surface of the insulating resin layer is roughened using a desmearing process such as permanganate treatment. At this stage, the surface roughness (Ra) of the roughened surface of the insulating resin layer is 300 nm or higher. Next, a copper seed layer is formed on the insulating resin layer using electroless plating. Then, a photoresist is formed on the portions of the seed layer where no wiring layers are formed. Furthermore, a thick copper plating layer is formed on the portions where no photoresist is formed by electroplating. Finally, after removing the photoresist, the exposed seed layer is etched. This creates a wiring pattern on the resin substrate consisting of the seed layer and the metal plating layer. Summary of the Invention The technical problem that the invention aims to solve
[0005] The purpose of this invention is to provide a novel copper component. Technical means to solve technical problems
[0006] [1] A copper component, wherein, The copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed. When the copper component is peeled off from the resin substrate after being hot-pressed onto it... The signal-to-noise ratio (S / N) of the peaks on the surface of the copper component corresponding to the material from the resin substrate was obtained by attenuated total reflectance absorption Fourier transform infrared spectroscopy (FT-IR / ATR method) in the wavelength range of 700 cm⁻¹. -1 -4000cm -1 Below 10 EDS elemental analysis revealed that the total metal content / (C+O) ratio on the surface of the resin substrate was greater than 0.4. The thickness of the seed layer formed in the resin substrate is 0.1 μm or more and 2.0 μm or less. [2] The copper component as described in [1], wherein the S / N ratio of the peak is 7 or less. [3] A copper component, wherein, The copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed. When the copper component is peeled off from the resin substrate after being hot-pressed onto it... X-ray photoelectron spectroscopy (XPS) survey spectrum analysis detected metal atoms contained in the copper oxide layer on the surface of the resin substrate after the copper component was removed. The total metal content (C+O) ratio on the surface of the resin substrate, as determined by EDS elemental analysis, is 0.4 or higher. The thickness of the seed layer formed in the resin substrate is 0.1 μm or more and 2.0 μm or less. [4] The copper component as described in [3], wherein, The sum of the main peak intensities of the metal elements detected from the surface of the resin substrate from which the copper component has been stripped is greater than the peak intensity of C1s. [5] The copper component as described in [4], wherein, On the surface of the resin substrate from which the copper component has been removed, the ratio of [total surface atomic percentage of metal elements (atom%)] / [surface atomic percentage of C1s (atom%)] calculated based on XPS measurements is 0.010 or higher. [6] The copper component as described in [4], wherein, The combined percentage of surface atomic composition of Cu2p3 and Ni2p3 detected by the Survey spectrum analysis was greater than 1.5 atom%. [7] The copper component as described in [4], wherein, The surface atomic composition percentage of Cu2p3 detected by the Survey spectrum analysis is above 1.0 atom%. [8] The copper component as described in any one of [1]-[7], wherein, The surface on which the layer containing the copper oxide is formed has a Ra of 0.04 μm or more, and the Ra of the surface of the copper component peeled off from the resin substrate is less than 100% relative to the above Ra. [9] The copper component as described in any one of [1]-[8], wherein, The surface area of the copper component peeled off from the resin substrate is less than 100% relative to the surface area of the surface on which the layer containing the copper oxide is formed.
[10] The copper component as described in any one of [1]-[9], wherein, The color difference (ΔE*ab) between the surface on which the layer containing the copper oxide is formed and the surface of the copper component peeled off from the resin substrate is 15 or more.
[11] The copper component as described in any one of [1]-
[10] , wherein, The resin substrate contains at least one insulating resin selected from the group consisting of polyphenylene oxide (PPE), epoxy resin, polyoxyethylene (PPO), polybenzoxazole (PBO), polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP) or thermoplastic polyimide (TPI), fluororesin, polyetherimide, polyetheretherketone, polycyclic olefin, bismaleimide resin, low dielectric constant polyimide and cyanate ester resin.
[12] The copper component as described in any one of [1]-
[11] , wherein, The copper component is hot-pressed onto the resin substrate under conditions of 50℃-400℃ temperature, 0MPa-20MPa pressure, and 1 minute-5 hours.
[13] The copper component as described in any one of [1]-
[12] , wherein, The layer containing the copper oxide contains a metal other than copper.
[14] The copper component as described in
[13] , wherein the metal other than copper is Ni.
[15] A selection method, wherein, The selection method is a method for selecting copper components, wherein the copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed, and the selection method includes: The process of hot-pressing the copper component to the resin substrate and then peeling it off from the resin substrate; The process of analyzing the surface of the copper component peeled from the resin substrate by attenuated total reflectance absorption Fourier transform infrared spectroscopy (FT-IR / ATR method). A process of performing EDS elemental analysis on the surface of the resin substrate from which the copper component has been removed; The process of measuring the thickness of the seed layer formed in the resin substrate after the copper component has been peeled off; and The process of selecting copper components The copper component satisfies the following condition: as obtained by the FT-IR / ATR method, the S / N ratio of the peak corresponding to the substance from the resin substrate on the surface of the copper component is within the wavelength range of 700 cm⁻¹. -1 -4000cm -1 The content of metals on the surface of the resin substrate is 10 or less; the composition ratio of total metals / (C+O) on the surface of the resin substrate is 0.4 or more, as obtained by EDS elemental analysis; the thickness of the seed layer is 0.1 μm or more and 2.0 μm or less.
[16] A selection method, wherein, The selection method is a method for selecting copper components, wherein the copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed, and the selection method includes: The process of hot-pressing the copper component to the resin substrate and then peeling it off from the resin substrate; The process of performing X-ray photoelectron spectroscopy (XPS) survey spectrum analysis on the surface of the copper component peeled off from the resin substrate; A process of performing EDS elemental analysis on the surface of the resin substrate from which the copper component has been removed; The process of measuring the thickness of the seed layer formed in the resin substrate after the copper component has been peeled off; and The process of selecting copper components The copper component satisfies the following conditions: metal atoms contained in the layer containing the copper oxide are detected on the surface of the resin substrate from which the copper component has been removed; the composition ratio of the total metal / (C+O) on the surface of the resin substrate is 0.4 or more, as determined by the EDS elemental analysis; and the thickness of the seed layer is 0.1 μm or more and 2.0 μm or less.
[17] The selection method as described in
[16] , wherein the selection method further comprises: The process of locally coating the surface of the copper component with a silane coupling agent or rust inhibitor; and The process of forming a layer containing the copper oxide by oxidizing the partially coated surface.
[18] The selection method as described in
[17] , wherein the surface of the copper component is oxidized by an oxidizing agent.
[19] The selection method as described in
[17] or
[18] , wherein, The silane coupling agent is selected from the group consisting of silane, tetraorganosilane, aminoethyl-aminopropyltrimethoxysilane, (3-aminopropyl)trimethoxysilane, (1-[3-(trimethoxysilyl)propyl]urea)((l-[3-(Trimethoxysilyl)propyl]urea)), (3-aminopropyl)triethoxysilane, (3-chloropropyl)trimethoxysilane, (3-glycidyl ether oxypropyl)trimethoxysilane, dimethyl dichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, triethoxy(isobutyl)silane, triethoxy(octyl)silane, tri(2-methoxyethoxy)(vinyl)silane, trichlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, trichlorotriethoxysilane, and ethylene-trimethoxysilane.
[20] The selection method as described in
[17] or
[18] , wherein the rust inhibitor is selected from 1H-tetrazole, 5-methyl-1H-tetrazole, 5-amino-1H-tetrazole, 5-phenyl-1H-tetrazole, 1,2,3-triazole, 1,2,4-triazole, 1,2,3-benzotriazole, 5-methyl-1H-benzotriazole, 5-amino-1H-benzotriazole, 2-mercaptobenzothiazole, 1,3-dimethyl-5-pyrazolone, pyrrole, 3 The group consisting of 1-methylpyrrole, 2,4-dimethylpyrrole, 2-ethylpyrrole, pyrazole, 3-aminopyrazole, 4-methylpyrazole, 3-amino-5-hydroxypyrazole, thiazole, 2-aminothiazole, 2-methylthiazole, 2-amino-5-methylthiazole, 2-ethylthiazole, benzothiazole, imidazole, 2-methylimidazolium, 2-ethylimidazolium, 2-butylimidazolium, 5-aminoimidazolium, 6-aminoimidazolium, benzimidazole, and 2-(methylthio)benzimidazole.
[21] The selection method as described in any one of
[17] -
[20] , wherein, The selection method further includes the following step: forming a layer containing a metal other than copper on the surface that has undergone the oxidation treatment.
[22] The selection method as described in
[21] , wherein the metal other than copper is Ni.
[23] The selection method as described in
[16] , wherein the selection method further comprises: The process of oxidizing the surface of the copper component; and The process of treating the surface that has undergone the oxidation treatment with a solvent to form a layer containing the copper oxide.
[24] The selection method as described in
[23] , wherein the surface of the copper component is oxidized by an oxidizing agent.
[25] The selection method as described in item
[23] , wherein, The solvent is selected from the group consisting of nickel chloride, zinc chloride, ferric chloride, chromium chloride, ammonium citrate, potassium chloride, ammonium sulfate, ammonium chloride, nickel ammonium sulfate, ethylenediaminetetraacetic acid, diethanolamine glycine, tetrasodium L-glutamic acid diacetate, ethylenediamine-N,N'-disuccinic acid, sodium 3-hydroxy-2,2'-iminodisuccinate, trisodium methylglycine diacetate, tetrasodium aspartic acid diacetate, disodium N-(2-hydroxyethyl)iminodisuccinate, sodium gluconate, tin(II) chloride, and citric acid.
[26] The selection method as described in any one of
[23] -
[25] , wherein, The selection method further includes the following step: forming a layer containing a metal other than copper on the surface treated with the solvent.
[27] The selection method as described in
[26] , wherein the metal other than copper is Ni.
[28] A method for manufacturing a copper component, wherein, The manufacturing method is a method for manufacturing copper parts as described in any one of [1]-
[14] , the manufacturing method comprising: 1) A process of locally coating the surface of a copper component with a silane coupling agent or a rust inhibitor; and 2) The process of forming a layer containing the copper oxide by oxidizing the partially coated surface.
[29] A method for manufacturing a copper component, wherein, The manufacturing method is the method for manufacturing the copper component as described in item
[13] or
[14] , the manufacturing method comprising: 1) A process of locally coating the surface of a copper component with a silane coupling agent or a rust inhibitor; 2) The process of forming a layer containing the copper oxide by oxidizing the partially coated surface; and 3) The process of forming a layer containing a metal other than copper on the surface that has undergone oxidation treatment.
[30] A method for manufacturing a copper component, wherein, The manufacturing method is a method for manufacturing copper parts as described in any one of [1]-
[14] , the manufacturing method comprising: 1) The step of forming a layer containing the copper oxide by oxidizing the partially coated surface; and, 2) The step of treating the surface that has undergone the oxidation treatment with a solvent.
[31] A method for manufacturing a copper component, wherein, The manufacturing method is the method for manufacturing the copper component as described in item
[13] or
[14] , the manufacturing method comprising: 1) A process of forming a layer containing the copper oxide by oxidizing the surface of the copper component; 2) The step of treating the surface that has undergone the oxidation treatment with a solvent; and 3) The process of forming a layer containing a metal other than copper on the surface treated with the solvent. The solvent contains components that dissolve the copper oxide.
[32] A method for manufacturing a copper component as described in
[30] or
[31] , wherein, The solvent contains a compound selected from the group consisting of nickel chloride, zinc chloride, ferric chloride, chromium chloride, ammonium citrate, potassium chloride, ammonium sulfate, ammonium chloride, nickel ammonium sulfate, ethylenediaminetetraacetic acid, diethanolamine glycine, tetrasodium L-glutamic acid diacetate, ethylenediamine-N,N'-disuccinic acid, sodium 3-hydroxy-2,2'-iminodisuccinate, trisodium methylglycine diacetate, tetrasodium aspartate diacetate, disodium N-(2-hydroxyethyl)iminodisuccinate, sodium gluconate, tin(II) chloride, and citric acid.
[33] A method for manufacturing a copper component as described in
[29] or
[31] , wherein the metal other than copper is Ni.
[0007] ==Cross-citation with relevant literature== This application claims priority based on Japanese Patent Application No. 2021-071460, filed on April 20, 2021, which is incorporated herein by reference. Attached Figure Description
[0008] Figure 1A This figure shows a scanning electron microscope (SEM) image of a cross-section taken in the manufacturing method (B) of the laminate in one embodiment of the present invention, comparing it with the prior art MSAP method. (A-1) and (B-1) represent the MSAP method, and (A-2) and (B-2) represent the method of this embodiment. Figure 1BThis is a schematic diagram of the seed layer according to an embodiment of the present invention. The gray portion represents the insulating substrate layer, and the black portion represents the portion of the copper component transferred to the insulating substrate layer. An example of case (A) and an example of case (B) are shown when the copper component is peeled from the insulating substrate layer, where (A) is the case where the copper component is peeled off exactly on the surface of the insulating substrate layer, and (B) is the case where the copper component is peeled off from the surface of the insulating substrate layer, inside the copper component compared to the protrusion. The two straight lines correspond to the surface of the peeled copper component and the position of the surface formed to include the bottom of the recess (the recess formed on the insulating substrate layer by the protrusion of the copper component), respectively. The portion enclosed by these two straight lines is the seed layer, and the distance between the two straight lines, indicated by the arrows, is the thickness of the seed layer. Figure 2 shows the visual observation results and representative photographs of the two side surfaces after the composite copper foils of Examples 1-6 and Comparative Examples 2-6 were pressed onto a resin substrate and peeled off. Visual observation results are recorded as follows: 0 indicates the copper foil surface has shifted towards the resin side, and × indicates no shift. Figure 3 is a graph showing the XPS analysis results of the resin substrates of Examples 1-3 and Comparative Examples 1-4. Figure 4 shows the surface results of the composite copper foils of Examples 1-3 and Comparative Examples 2-4 after hot pressing onto a resin substrate (R5670KJ) and peeling, measured by FT-IR / ATR method. Figure 5 The results were obtained by measuring the surface of the composite copper foil by FT-IR / ATR after hot-pressing the composite copper foil of Example 3 and Comparative Example 3 onto a resin substrate (R1551GG) and peeling it off. Figure 6 shows the results of measuring the surface of the composite copper foil by FT-IR / ATR after hot-pressing the composite copper foils of Examples 4-6 and Comparative Examples 5-6 onto a resin substrate (R5680J) and then peeling them off. Figure 7 The results were obtained by measuring the surface of the composite copper foil by FT-IR / ATR after hot-pressing the composite copper foil of Example 3 and Comparative Example 3 onto a resin substrate (NX9255) and then peeling it off. Figure 8 The results were obtained by measuring the surface of the composite copper foil by FT-IR / ATR after hot-pressing the composite copper foil of Example 3 and Comparative Example 3 onto the resin substrate (CT-Z) and then peeling it off. Figure 9 It is a secondary electron image of the resin substrate surface and an EDS image of Cu obtained by hot-pressing composite copper foil onto a resin substrate and then peeling it off, using a field emission scanning electron microscope. Figure 10The images are SEM images of the seed layer cross-section formed on the resin substrate after hot-pressing the composite copper foils of Examples 1, 2, 3, 3, and Comparative Examples 3 and 7 onto a resin substrate and then peeling them off. Figure 11 The images are SEM images (30,000x magnification) of cross sections observed after resin plating treatment of the seed layers of Examples 1, 2, 3 and Comparative Example 7. Detailed Implementation
[0009] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, but are not necessarily limited thereto. Furthermore, the objects, features, advantages, and concepts of the present invention will be clear to those skilled in the art from the description herein, and those skilled in the art can readily reproduce the present invention from this description. The embodiments and specific examples described below illustrate preferred embodiments of the present invention and are for illustrative purposes only, and are not intended to limit the present invention to these embodiments. Various changes and modifications can be made to the present invention within the intent and scope disclosed in this specification, as will be apparent to those skilled in the art.
[0010] ==Manufacturing Method of Laminated Insulating Substrate Layer and Copper Components== One embodiment disclosed in this specification is a manufacturing method for a laminate of an insulating substrate layer and a copper component, comprising: a step of bonding an insulating substrate layer and a copper component having protrusions on its surface; a step of transferring the protrusions to the surface of the insulating substrate layer by peeling off the copper component to form a seed layer; a step of forming a photoresist at a predetermined position on the surface of the seed layer; a step of laminating copper by copper plating on the surface of the seed layer where the photoresist is not laminated; a step of removing the photoresist; and a step of removing the exposed seed layer by removing the photoresist. Furthermore, in this specification, the seed layer refers to the layer formed between "the surface of the peeled-off copper component" and "the surface constructed to include the bottom of the recess (formed by the protrusions of the copper component on the insulating substrate layer)". Figure 1B Therefore, the recess and the metal from the copper component transferred to the recess are contained in the layer. The bottom of the recess refers to the bottom of the plurality of recesses that is furthest from the surface of the stripped copper component, and the surface formed to contain the bottom of the recess is parallel to the surface of the stripped copper component.
[0011] [1] The process of bonding the insulating substrate layer and the copper component <Copper Components> The surface of the copper component has fine protrusions. The arithmetic mean roughness (Ra) of the surface of the copper component is preferably 0.03 μm or more, more preferably 0.05 μm or more, and preferably 0.3 μm or less, more preferably 0.2 μm or less.
[0012] The maximum surface roughness (Rz) of the copper component is preferably 0.2 μm or more, more preferably 1.0 μm or more, and preferably 2.0 μm or less, more preferably 1.7 μm or less.
[0013] If Ra and Rz are too small, the adhesion to the resin substrate will be insufficient; if they are too large, the formation of fine wiring and high-frequency characteristics will deteriorate.
[0014] Here, the arithmetic mean roughness (Ra) represents the average of the absolute values of Z(x) (i.e., the height of the convex portion and the depth of the concave portion) in the profile curve (y=Z(x)) expressed by the following formula at the reference length l.
[0015] The maximum height roughness (Rz) represents the sum of the maximum value of the convex height Zp and the maximum value of the concave depth Zv of the profile curve (y=Z(x)) under the reference length l.
[0016] Ra and Rz can be calculated according to the method specified in JIS B 0601:2001 (based on international standard ISO4287-1997).
[0017] The average length (RSm) of the surface roughness profile element of the copper component is not particularly limited, but is preferably below 1500 nm, 1400 nm, 1300 nm, 1200 nm, 1100 nm, 1000 nm, 900 nm, 800 nm, 750 nm, 700 nm, 650 nm, 600 nm, 550 nm, 450 nm, or 350 nm, and preferably above 100 nm, 200 nm, or 300 nm. Here, RSm represents the average length of the roughness profile element (i.e., the length of the profile profile element: Xs1-Xsm) of one cycle of the roughness profile contained in a certain reference length (lr), and is calculated by the following formula.
[0018] Here, 10% of the arithmetic mean roughness (Ra) is taken as the minimum height in the undulation, and 1% of the reference length (lr) is taken as the minimum length, thus defining the undulation of one cycle. As an example, RSm can be measured and calculated according to "Method for determination of surface roughness of fine ceramic thin films according to atomic force microscopy (JIS R 1683:2007)".
[0019] The copper component has a layer containing copper oxide formed on at least a portion of its surface. Specifically, the copper component is copper foil, copper wire, copper plate, copper lead frame, etc., such as electrolytic copper foil, rolled copper foil, and copper foil with carrier, but is not limited to these. The copper component contains copper as a main component and is part of the structure. It is preferably made of pure copper with a Cu purity of 99.9% by mass or more, more preferably formed of ductile copper, deoxidized copper, or oxygen-free copper, and even more preferably formed of oxygen-free copper with an oxygen content of 0.001% to 0.0005% by mass.
[0020] When the copper component is made of copper foil, its thickness is not particularly limited, but is preferably 0.1 μm or more and 100 μm or less, and more preferably 0.5 μm or more and 50 μm or less.
[0021] <Manufacturing Methods for Copper Components> A copper oxide layer is formed on the surface of the copper component, containing copper oxide (CuO) and / or cuprous oxide (Cu2O). This copper oxide layer can be formed by oxidizing the surface of the copper component. Through this oxidation process, the surface of the copper component is roughened.
[0022] While a roughening process such as soft etching or etching is not mandatory before the oxidation process, it can still be performed. Additionally, degreasing, acid cleaning (to homogenize the surface by removing the natural oxide film), or alkaline treatment (to prevent acid from contaminating the oxidation process after acid cleaning) can also be performed before oxidation. The method of alkaline treatment is not particularly limited; preferably, a 0.1 g / L-10 g / L, more preferably 1 g / L-2 g / L alkaline aqueous solution, such as a sodium hydroxide aqueous solution, can be used at 30-50°C for approximately 0.5 to 2 minutes.
[0023] The oxidizing agent is not particularly limited; for example, aqueous solutions of sodium chlorite, sodium hypochlorite, potassium chlorate, and potassium perchlorate can be used. Various additives (such as phosphates like trisodium phosphate dodecahydrate) and surfactant molecules can be added to the oxidizing agent. Examples of surfactant molecules include porphyrins, macroporphyrins, extended porphyrins, cyclic porphyrins, linear porphyrin polymers, porphyrin sandwich coordination complexes, porphyrin arrays, silanes, tetraorganosilanes, aminoethyl-aminopropyltrimethoxysilane, (3-aminopropyl)trimethoxysilane, (1-[3-(trimethoxysilyl)propyl]urea)((l-[3-(Trimethoxysilyl)propyl]urea)), and (3-aminopropyl)trimethoxysilane. The oxidizing agents include triethoxysilane, (3-chloropropyl)trimethoxysilane, (3-glycidyl etheroxypropyl)trimethoxysilane, dimethyldichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, triethoxy(isobutyl)silane, triethoxy(octyl)silane, tris(2-methoxyethoxy)(vinyl)silane, trichlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, chlorotriethoxysilane, ethylene-trimethoxysilane, amines, sugars, etc. The oxidation reaction conditions are not particularly limited, but the preferred temperature of the test solution for oxidation is 40-95°C, more preferably 45-80°C. The preferred reaction time is 0.5-30 minutes, more preferably 1-10 minutes.
[0024] For layers containing copper oxides, a solvent can also be used to adjust the protrusions on the surface of the oxidized copper component. The solvent used in this dissolution process is not particularly limited, but chelating agents, especially biodegradable chelating agents, are preferred. Examples include ethylenediaminetetraacetic acid (EDTA), diethanolglycine, tetrasodium L-glutamic acid diacetate, ethylenediamine-N,N'-disuccinic acid, sodium 3-hydroxy-2,2'-iminodisuccinate, trisodium methylglycine diacetate, tetrasodium aspartic acid diacetate, disodium N-(2-hydroxyethyl)iminodisuccinate, and sodium gluconate. The pH of the dissolving solution is not particularly limited, but alkaline is preferred, more preferably pH 8-pH 10.5, further preferably pH 9.0-pH 10.5, and even more preferably pH 9.8-pH 10.2.
[0025] Alternatively, the surface of the copper oxide-containing layer can be reduced using a reducing agent, in which case cuprous oxide can be formed on the surface of the copper oxide-containing layer. Examples of reducing agents used in this reduction process include dimethylamine borane (DMAB), diborane, sodium borohydride, and hydrazine.
[0026] Its resistivity relative to pure copper is 1.7 × 10⁻⁶. -8(Ωm), copper oxide is 1-10 (Ωm), cuprous oxide is 1×10 6 -1×10 7 (Ωm), therefore the conductivity of the copper oxide layer is low. For example, even if a large amount of copper oxide layer is transferred to the resin substrate, transmission loss caused by the skin effect is not likely to occur when the copper component of the present invention is used to form a circuit of a printed wiring substrate or a semiconductor packaging substrate.
[0027] The layer containing copper oxide may contain metals other than copper. The metals contained are not particularly limited, and may include at least one metal selected from the group consisting of Sn, Ag, Zn, Al, Ti, Bi, Cr, Fe, Co, Ni, Pd, Au, and Pt. In particular, for acid and heat resistance, it is preferable to contain metals with higher acid and heat resistance than copper, such as Ni, Pd, Au, and Pt.
[0028] A layer containing a metal other than copper can also be formed on top of a layer containing copper oxide. This layer can be formed on the outermost surface of the copper component by plating. The plating method is not particularly limited; for example, metals other than copper, such as Sn, Ag, Zn, Al, Ti, Bi, Cr, Fe, Co, Ni, Pd, Au, Pt, or various alloys, can be used for plating by electroplating, electroless plating, vacuum evaporation, chemical conversion treatment, etc.; it is preferable to form a plating layer of the same thinness, therefore electroplating is preferred.
[0029] In the case of electroplating, nickel plating and nickel alloy plating are preferred. Examples of metals formed by nickel plating and nickel alloy plating include pure nickel, Ni-Cu alloy, Ni-Cr alloy, Ni-Co alloy, Ni-Zn alloy, Ni-Mn alloy, Ni-Pb alloy, and Ni-P alloy.
[0030] Examples of metal salts used for plating include nickel sulfate, nickel sulfamate, nickel chloride, nickel bromide, zinc oxide, zinc chloride, dichlorodiammonium palladium, ferric sulfate, ferric chloride, chromic anhydride, chromium chloride, sodium chromium sulfate, copper sulfate, copper pyrophosphate, cobalt sulfate, and manganese sulfate.
[0031] In nickel plating, the bath composition preferably contains, for example, nickel sulfate (more than 100 g / L and less than 350 g / L), nickel aminosulfonate (more than 100 g / L and less than 600 g / L), nickel chloride (more than 0 g / L and less than 300 g / L), and mixtures of these substances. Sodium citrate (more than 0 g / L and less than 100 g / L) and boric acid (more than 0 g / L and less than 60 g / L) may also be included as additives.
[0032] When electroplating is applied to the surface of anodized copper foil, the copper oxide on the surface is first reduced to cuprous oxide or pure copper, thereby consuming charge and creating a time delay before plating. Afterward, the metal to form the metal layer begins to precipitate. The amount of charge varies depending on the type of plating solution and the amount of copper oxide. For example, when plating Ni onto a copper component, in order to control its thickness within a preferred range, it is preferable to have a minimum thickness of dm² per unit area of the electroplated copper component. 2 The charge is applied to the material with a charge of 10C or more and 90C or less, more preferably with a charge of 20C or more and 65C or less.
[0033] The amount of metal deposited on the outermost surface of the copper component by plating is not particularly limited, but is preferably 0.8 mg / dm³. 2 -6.0mg / dm 2 Alternatively, the amount of metal attached can be calculated, for example, by dissolving it in an acidic solution, determining the amount of metal by ICP analysis, and then dividing by the planar field of view of the structure.
[0034] To facilitate the breakage of the copper oxide-containing layer from the copper component, steps 1) and 2) can be performed: 1) Before oxidation treatment, a coating agent such as a silane coupling agent or corrosion inhibitor is applied to the surface of the copper component; 2) After oxidation treatment, the copper oxide-containing layer is treated with a solvent. Applying a coating agent such as a silane coupling agent or corrosion inhibitor to the surface of the copper component protects that area from oxidation, creating voids in the copper oxide-containing layer, making it easier for the layer to break off from the copper component. Here, the solvent is a reagent that dissolves copper oxides. Treatment with the solvent causes partial dissolution of the copper oxides near the interface between the copper component and the copper oxide-containing layer, making it easier for the layer to break off from the copper component.
[0035] The silane coupling agent is not particularly limited and can be selected from silanes, tetraorganosilanes, aminoethyl-aminopropyltrimethoxysilane, (3-aminopropyl)trimethoxysilane, (1-[3-(trimethoxysilyl)propyl]urea)((l-[3-(Trimethoxysilyl)propyl]urea)), (3-aminopropyl)triethoxysilane, (3-chloropropyl)trimethoxysilane, (3-glycidyl ether oxypropyl)trimethoxysilane, dimethyl dichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, triethoxy(isobutyl)silane, triethoxy(octyl)silane, tri(2-methoxyethoxy)(vinyl)silane, trichlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, trichlorotriethoxysilane, and ethylene-trimethoxysilane.
[0036] There are no particular limitations on the rust inhibitor; it can be selected from 1H-tetrazole, 5-methyl-1H-tetrazole, 5-amino-1H-tetrazole, 5-phenyl-1H-tetrazole, 1,2,3-triazole, 1,2,4-triazole, 1,2,3-benzotriazole, 5-methyl-1H-benzotriazole, 5-amino-1H-benzotriazole, 2-mercaptobenzothiazole, 1,3-dimethyl-5-pyrazolone, pyrrole, 3-methylpyrrole, etc. 2,4-Dimethylpyrrole, 2-Ethylpyrrole, Pyrazole, 3-Aminopyrazole, 4-Methylpyrazole, 3-Amino-5-hydroxypyrazole, Thiazole, 2-Aminothiazole, 2-Methylthiazole, 2-Amino-5-methylthiazole, 2-Ethylthiazole, Benzothiazole, Imidazole, 2-Methylimidazol, 2-Ethylimidazol, 2-Butylimidazol, 5-Aminoimidazol, 6-Aminoimidazol, Benzimidazole, 2-(Methylthio)benzimidazole.
[0037] Treatment with silane coupling agents or preservatives can be performed at any time before oxidation, or it can be done together with degreasing, acid cleaning (to homogenize the surface by removing the natural oxide film), or alkali treatment (to prevent acid from being introduced into the oxidation process after acid cleaning). The surface of the copper component is preferably partially coated by treatment with a silane coupling agent or corrosion inhibitor (e.g., 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% or more, but less than 100%). Therefore, it is preferred to react at a concentration of 0.1%, 0.5%, 1%, or 2% or more at room temperature for 30 seconds, 1 minute, or 2 minutes or more.
[0038] The solvent used to facilitate the breakage of copper oxide-containing layers from copper components only needs to contain components that dissolve copper oxides. It is not limited to nickel chloride and can be selected from chlorides (potassium chloride, zinc chloride, ferric chloride, chromium chloride, etc.), ammonium salts (ammonium citrate, ammonium chloride, ammonium sulfate, nickel ammonium sulfate, etc.), chelating agents (ethylenediaminetetraacetic acid, diethanolglycine, tetrasodium L-glutamic acid diacetate, ethylenediamine-N,N'-disuccinic acid, sodium 3-hydroxy-2,2'-iminodisuccinate, trisodium methylglycine diacetate, tetrasodium aspartic acid diacetate, disodium N-(2-hydroxyethyl)iminodisuccinate, sodium gluconate, etc.), tin(II) chloride, and citric acid.
[0039] When using nickel chloride for treatment, there are no particular limitations, but it is preferable to immerse the copper component with a copper oxide layer formed in a nickel chloride solution (concentration 45 g / L or higher) at room temperature or above for at least 5 seconds. Furthermore, nickel chloride treatment can be performed alone, simultaneously with oxidation treatment, or after oxidation treatment and simultaneously with plating treatment. For example, the plating solution can contain nickel chloride, and before plating, the copper component with a copper oxide layer formed can be immersed in the plating solution for 5 seconds, 10 seconds, 15 seconds, 20 seconds, 30 seconds, 1 minute, or 2 minutes. The immersion time can be appropriately varied depending on the oxide film thickness.
[0040] <Insulating Substrate Layer> The substrate for the insulating substrate layer is not particularly limited as long as the surface contour of the copper component with its uneven shape is transferred onto the resin substrate when the copper component with its uneven surface is adhered to the insulating substrate layer. A resin substrate is preferred. The resin substrate is a material containing resin as its main component. The type of resin is not particularly limited; it can be a thermoplastic resin or a thermosetting resin. Examples include polyphenylene ether (PPE), epoxy resin, polymethyl methacrylate (PPO), polybenzoxazole (PBO), polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), thermoplastic polyimide (TPI), fluororesin, polyetherimide, polyetheretherketone, polycyclic olefin, bismaleimide resin, low dielectric constant polyimide, cyanate ester resin, or a mixture of these substances. The resin substrate may further contain inorganic fillers or glass fibers. The relative permittivity of the insulating substrate layer used is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.8 or less.
[0041] <fit> When a copper component with an uneven surface is bonded to an insulating substrate layer, the surface contour of the copper component, containing uneven shapes, is transferred onto the resin substrate. Therefore, recesses complementary to the protrusions on the surface of the insulating substrate layer, and protrusions complementary to the recesses, are formed on the surface of the insulating substrate layer.
[0042] There are no particular limitations on the bonding method, but thermal press fitting is preferred. To thermally press the resin substrate onto the surface of the copper component, for example, the resin substrate and the copper component are laminated together, followed by heat treatment under specified conditions. The specified conditions (e.g., temperature, pressure, time, etc.) can also be the recommended conditions of each substrate manufacturer. The specified conditions may include, for example, the following.
[0043] 1) When the resin substrate contains epoxy resin or is composed of epoxy resin, it is preferable to heat-press the copper parts to the resin substrate by applying a pressure of 0MPa-20MPa at a temperature of 50°C-300°C for 1 minute to 5 hours.
[0044] For example: 1-1) With the resin substrate being R-1551 (manufactured by Panasonic), heat at 1 MPa pressure to 100°C, hold at that temperature for 5-10 minutes, then heat further at 3.3 MPa pressure to 170-180°C, hold at that temperature for 50 minutes, thereby performing hot pressing.
[0045] 1-2) With the resin substrate being R-1410A (manufactured by Panasonic), heat at 1 MPa to 130°C, hold at that temperature for 10 minutes, then heat further at 2.9 MPa to 200°C, hold at that temperature for 70 minutes, thereby performing hot pressing.
[0046] 1-3) When the resin substrate is EM-285 (manufactured by EMC), heat it at a pressure of 0.4MPa to reach 100°C, then increase the pressure to 2.4MPa-2.9MPa and heat it further to reach 195°C. Hold it at this temperature for 50 minutes to perform hot pressing.
[0047] 1-4) When the resin substrate is GX13 (manufactured by Ajinomoto), heat is applied at 1.0 MPa while heating, and the temperature is maintained at 180°C for 60 minutes to perform hot pressing.
[0048] 2) When the resin substrate contains PPE resin or is composed of PPE resin, it is preferable to heat-press the copper parts to the resin substrate by applying a pressure of 0MPa-20MPa at a temperature of 50°C-350°C for 1 minute to 5 hours.
[0049] For example: 2-1) When the resin substrate is R5620 (manufactured by Panasonic), hot pressing is performed while heating to 100°C under a pressure of 0.5MPa. Then, the temperature and pressure are increased and maintained at 2.0MPa-3.0MPa and 200°C-210°C for 120 minutes, thereby further hot pressing is performed.
[0050] 2-2) With the resin substrate being R5670KJ (manufactured by Panasonic), hot pressing was performed while heating to 110°C under a pressure of 0.49MPa. Then, the temperature and pressure were increased and maintained at 2.94MPa and 210°C for 120 minutes to perform hot pressing.
[0051] 2-3) When the resin substrate is R5680J (manufactured by Panasonic), hot pressing is performed while heating to 110°C under a pressure of 0.5MPa. Then, the temperature and pressure are increased and maintained at 3.0MPa-4.0MPa and 195°C for 75 minutes to perform hot pressing.
[0052] 2-4) When the resin substrate is N-22 (manufactured by Nelco), heat is applied while pressing at 1.6MPa-2.3MPa, and after holding at 177°C for 30 minutes, further heating is carried out and held at 216°C for 60 minutes, thereby performing hot pressing.
[0053] 3) When the resin substrate contains PTFE resin or is composed of PTFE resin, it is preferable to heat-press the copper parts to the resin substrate by applying a pressure of 0MPa-20MPa at a temperature of 50°C-400°C for 1 minute to 5 hours.
[0054] For example: 3-1) With the resin substrate being NX9255 (manufactured by Park Electroke Mikael), heat to 260°C while applying pressure at 0.69 MPa, increase the pressure to 1.03 MPa-1.72 MPa, heat to 385°C, and hold at 385°C for 10 minutes to perform hot pressing.
[0055] 3-2) When the resin substrate is RO3003 (manufactured by Ross), after 50 minutes of pressure application (approximately 220°C), the pressure is increased to 2.4 MPa and held at 371°C for 30-60 minutes to perform heat bonding.
[0056] 4) When the resin substrate contains liquid crystal polymer (LCP) or is composed of LCP, it is preferable to hot-press the copper component to the resin substrate by applying a pressure of 0MPa-20MPa at a temperature of 50°C-400°C for 1 minute to 5 hours. For example, when the resin substrate is CT-Z (Kurare Manufacturing), it is heated at a pressure of 0MPa, held at 260°C for 15 minutes, and then further heated while applying pressure at 4MPa, held at 300°C for 10 minutes, thereby performing hot pressing.
[0057] [2] Process of stripping copper components After the copper component is bonded to the insulating substrate layer, it is peeled off from the insulating substrate layer under specified conditions. The protrusions on the surface of the copper component are transferred to the insulating substrate layer, forming a seed layer on the surface of the insulating substrate layer. Therefore, the surface of the insulating substrate layer becomes flat.
[0058] The seed layer thickness should be 2.50 μm or less, more preferably 2.00 μm or less, and even more preferably 1.70 μm or less. It is also preferred to be 0.01 μm or more, more preferably 0.10 μm or more, and even more preferably 0.36 μm or more. If the thickness is less than 0.01 μm, the plating formation is poor, and the adhesion to the insulating substrate decreases. If it exceeds 2.50 μm, the wiring formation deteriorates. Furthermore, the method for measuring the seed layer thickness is not particularly limited; for example, the thickness can be measured in an SEM image.
[0059] In the method disclosed herein, the seed layer thus fabricated is directly used as part of the circuit. No process of removing the bumps (the bumps transferred to the surface of the copper component in the insulating substrate layer) occurs, thereby achieving good adhesion between the copper and the insulating substrate layer.
[0060] There are no particular restrictions on the conditions for peeling copper components from the resin substrate; a 90° peel test can be performed (Japanese Industrial Standard (JIS) C5016 "Test Method for Flexible Printed Wiring Boards"; corresponding international standards IEC249-1:1982, IEC326-2:1990). There are also no particular restrictions on the method for peeling copper components from the insulating substrate layer; it can be done mechanically or manually.
[0061] Various methods, such as X-ray photoelectron spectroscopy (XPS), energy dispersive X-ray spectroscopy (EDS), and inductively coupled plasma atomic emission spectrometry (ICP-OES / ICP-AES), can be used to detect metals transferred to the surface of the insulating substrate layer after the copper component has been stripped. For example, metals contained in the copper oxide layer can be transferred onto the insulating substrate layer (which is the insulating substrate layer after the copper component has been stripped, and the surface of the copper component has a layer containing copper oxide).
[0062] XPS involves irradiating an object with X-rays and capturing the photoelectrons emitted as the object ionizes. - This is a method for energy analysis. XPS can be used to investigate the types, amounts, and chemical bonding states of elements present on the sample surface or at a specified depth (e.g., up to 6 nm). The diameter of the analysis point (i.e., the diameter of the cross-section when cutting a cylindrical portion that can be analyzed with a circular cross-section) is preferably between 1 μm and 1 mm. Here, XPS surveyspectrum analysis is used to detect metal atoms contained in the copper oxide layer on the surface of the insulating substrate from which the copper component has been peeled off.
[0063] The metal contained in the protrusions of the copper component is preferably transferred to the insulating substrate layer in a manner that fills 70% or more, 80% or more, 90% or more, 95% or more, 99% or more, or 99.9% or more of the recesses in the transferred surface contour. If the metal fills most of the recesses in the insulating substrate layer, the sum of the peak intensities of the main spectral peaks of the metal atoms is greater than the peak intensity of the main spectral peak of C1s when the surface of the insulating substrate layer is measured by XPS. The main peak refers to the peak with the highest intensity among the multiple peaks of the metal element. For example, the peak of the 2p3 orbital is the main peak in Cu, the peak of the 3d5 orbital is the main peak in Sn, the peak of the 3d5 orbital is the main peak in Ag, the peak of the 2p3 orbital is the main peak in Zn, the peak of the 2p orbital is the main peak in Al, the peak of the 2p3 orbital is the main peak in Ti, the peak of the 4f7 orbital is the main peak in Bi, the peak of the 2p3 orbital is the main peak in Cr, the peak of the 2p3 orbital is the main peak in Fe, the peak of the 2p3 orbital is the main peak in Co, the peak of the 2p3 orbital is the main peak in Ni, the peak of the 3d5 orbital is the main peak in Pd, the peak of the 4f7 orbital is the main peak in Au, and the peak of the 4f7 orbital is the main peak in Pt. Furthermore, the intensity of the spectral peaks mentioned here refers to the vertical axis height of the XPS spectral data.
[0064] The percentage of Cu2p3 relative to the total atomic composition of the insulating substrate layer on which the copper component has been stripped, as measured by XPS, is preferably 1.0 atom% or more, 1.8 atom% or more, 2.8 atom% or more, 3.0 atom% or more, 4.0 atom% or more, 5.0 atom% or more, or 6.0 atom% or more. Alternatively, when measuring the surface of the transferred copper component by XPS, the ratio of the percentage of surface atomic composition of Cu2p3 to the percentage of surface atomic composition of C1s is preferably 0.010 or more, 0.015 or more, 0.020 or more, 0.025 or more, 0.030 or more, 0.035 or more, 0.040 or more, 0.045 or more, 0.050 or more, or 0.10 or more.
[0065] When the protrusion of the copper component contains metals other than copper, X-ray photoelectron spectroscopy (XPS) determines that the total atomic percentage of metal atoms on the surface of the stripped insulating substrate layer is 1.0 atom% or more, 1.5 atom% or more, 1.8 atom% or more, 2.8 atom% or more, 3.0 atom% or more, 4.0 atom% or more, 5.0 atom% or more, or 6.0 atom%. Alternatively, the ratio of (total atomic percentage of metal atoms on the surface of the stripped insulating substrate layer) / (atomic percentage of C1s on the surface of the stripped insulating substrate layer) is preferably 0.010 or more, 0.015 or more, 0.020 or more, 0.025 or more, 0.030 or more, 0.035 or more, 0.040 or more, 0.045 or more, 0.050 or more, or 0.10 or more.
[0066] Furthermore, regarding the elemental composition of the insulating substrate layer surface after the copper component has been stripped, as determined by EDS, the proportion of Cu is only 1 atom% or more, preferably 4 atom% or more, more preferably 7 atom% or more, even more preferably 10 atom% or more, and even more preferably 11.4 atom% or more. The higher the proportion of Cu, the better the transfer efficiency of the raised portion of the copper component and the better the plating formation. Here, transfer efficiency refers to the proportion of metal contained in the protrusion formed on the copper component that is transferred to the insulating substrate layer.
[0067] Furthermore, the ratio of the total metal content to (C+O) on the surface of the insulating substrate layer from which the copper component has been stripped, as determined by EDS, only needs to be 0.38 or higher, preferably 0.40 or higher, more preferably 0.42 or higher, and even more preferably 0.43 or higher. The lower the metal / (C+O) ratio, the worse the plating formation. A high C ratio indicates poor transfer efficiency, while a high O ratio indicates that plating adhesion is hindered.
[0068] The amount of substance from the insulating substrate layer detected on the surface of the copper component peeled off from the insulating substrate layer is preferably below the detection limit, or even if detected, it is in small amounts. This is because, in this case, breakage of the insulating substrate layer can be sufficiently suppressed during the peeling of the copper component. There are no particular limitations on the detection method for the substance from the insulating substrate layer, as long as a method suitable for the target substance is used. For example, in the case of organic matter, peaks from the insulating substrate layer can be detected using attenuated total reflectance absorption Fourier transform infrared spectroscopy (FT-IR) ("Infrared and Raman Spectroscopy: Principles and Spectral Interpretation" by Peter Larkin). FT-IR is an infrared spectroscopy method that identifies and / or quantifies compounds by irradiating the target substance with infrared light and utilizing the infrared absorption spectrum in the wavelength range of 700 cm⁻¹. -1 -4000cm -1 The S / N ratio is preferably 10 or less, 9 or less, more preferably 8 or less, 7 or less, and preferably no peak from the resin substrate is detected.
[0069] The proportion of Ra after peeling, relative to the Ra of the copper component surface before bonding with the layer with protrusions, is preferably less than 100%, less than 96%, less than 95%, less than 94%, less than 93%, less than 92%, less than 91%, less than 90%, less than 80%, less than 70%, less than 65%, or less than 60%. The smaller this proportion, the more metal from the layer with protrusions is transferred to the insulating substrate layer.
[0070] The percentage of the surface area after peeling, relative to the surface area of the copper component before bonding (where the layer with protrusions is formed), is preferably less than 100%, less than 98%, less than 97%, less than 96%, less than 95%, less than 94%, less than 93%, less than 92%, less than 91%, less than 90%, less than 80%, or less than 75%. A smaller percentage means that more metal from the layer with protrusions is transferred to the insulating substrate layer. Furthermore, the surface area can be measured using confocal microscopy or atomic force microscopy.
[0071] The ΔE*ab of the copper component surface before hot pressing and the copper component surface after peeling is preferably 13 or more, 15 or more, 20 or more, 25 or more, 30 or more, or 35 or more. The larger the difference, the more metal forming the protrusion is transferred to the insulating substrate layer.
[0072] In conventional SAP methods, as described above, the adhesion between the resin substrate and the seed layer is improved by forming bumps and depressions on the resin to act as anchors. However, this process creates relatively large bumps and depressions on the surface to ensure adhesion. Consequently, copper is deposited from the resin surface layer into the deeper layers, leaving trace amounts of copper residue during etching to remove the seed layer. These residual trace amounts of copper can cause short circuits between wirings, thus requiring deep etching. Furthermore, regarding the increased adhesion effect brought about by bump forming and electroless copper plating (electrolytic copper plating film), the choice of resin substrate is highly selective; only a few resin substrates, such as ABF (Ajinomoto Build-Up Film), can achieve sufficient adhesion.
[0073] Current MSAP methods use extremely thin copper foil with a carrier. From a processing perspective, the thickness of this extremely thin copper foil layer needs to be at least 1.5 μm, and a roughening treatment of at least 1 μm is required. By forming a seed layer with this roughening treatment on the resin, the adhesion between the resin substrate and the seed layer is improved. However, since a copper layer several μm thick containing the extremely thin copper foil layer and the roughened area needs to be removed, a deep etching process is required.
[0074] However, in recent years, the etching of large amounts of copper in fine patterns has led to pattern errors and pattern disappearance due to side etching. In addition, since the wiring layer is formed on the roughened surface of the resin substrate, the large unevenness can easily cause transmission loss of high-frequency signals.
[0075] Compared to the roughening processes performed by descaling in conventional SAP methods and the roughening of extremely thin copper foils with carriers in conventional MSAP methods, the seed layer obtained by the method disclosed in this invention has a low surface roughness. Therefore, it avoids problems such as copper residue after etching, pattern errors caused by side etching in micro-patterns, and transmission loss of high-frequency signals due to unevenness. In addition, although the surface roughness is low, the dense presence of micro-undulations ensures sufficient adhesion between the insulating substrate and the copper.
[0076] [3] The process of forming a resist at a specified position on the surface of the seed layer. After the copper components are stripped, resist is formed at designated locations on the surface of the seed layer. The locations where the resist is formed are the parts where copper is not subsequently laminated (as part of the circuitry).
[0077] The resist may contain materials that are cured or dissolved by photosensitive material, without particular limitation, but is preferably formed from dry film resist (DFR), positive liquid resist or negative liquid resist.
[0078] The DFR preferably contains an adhesive polymer that aids in film formation, as well as monomers (e.g., acrylate or methacrylate monomers) and a photopolymerization initiator that induce a photopolymerization reaction upon UV irradiation. The DFR is preferably formed using a dry film with a three-layer structure of coating / photoresist / carrier film. The photoresist is thermally laminated onto the structure while the coating is being peeled off; after lamination, the carrier film is peeled off, thereby forming the photoresist, i.e., the DFR, on the structure.
[0079] Examples of liquid photoresists include phenolic varnish resins, which are soluble in organic solvents. Liquid photoresists can be dissolved or cured by light irradiation after being applied to the surface of a structure and dried, thus forming a photoresist.
[0080] There is no particular limitation on the thickness of the resist, but 1μm-200μm is preferred.
[0081] A second seed layer can be formed by plating the surface of the seed layer after its formation and before the formation of the resist. The plating method is not particularly limited; it can be electroplating or electroless plating. For example, a metal selected from Ni, Sn, Al, Cr, Co, and Cu can be used to form a film through a known electroless plating method. Here, the second seed layer refers to the metal thin film formed by the plating process. The thickness of the second seed layer is not particularly limited and can be approximately 0.02 μm to 2 μm, but preferably, the total thickness of the seed layer and the seed layer on the surface of the insulating substrate layer is less than 2.5 μm.
[0082] [4] Copper lamination process Next, copper is laminated onto the surface of the seed layer, i.e., the area where the resist is not laminated. This laminated copper then functions as a circuit. There are no particular limitations on the method of copper plating; any known method can be used for the plating process.
[0083] [5] Removal process of resist There are no particular limitations on the method for removing the resist. Known methods such as using fuming nitric acid, sulfuric acid-hydrogen peroxide water mixture (sulfuric acid peroxide), or dry resist removal using O2 plasma can be used.
[0084] [6] Seed layer removal process There are no particular limitations on the method for removing the seed layer. For example, known methods such as rapid etching or flash etching using sulfuric acid-hydrogen peroxide etchants can be used.
[0085] ==Selection Methods for Copper Components== One embodiment of the present invention is a selection method for selecting a copper component having a copper oxide layer formed on at least a portion of its surface. The method includes: a step of peeling the copper component from a resin substrate after hot-pressing it to the resin substrate; a step of analyzing the surface of the peeled copper component using attenuated total reflectance absorption Fourier transform infrared spectroscopy (FT-IR / ATR); a step of performing EDS elemental analysis on the surface of the resin substrate from which the copper component has been peeled; a step of measuring the thickness of the seed layer formed in the resin substrate from which the copper component has been peeled; and a step of selecting the copper component, wherein the copper component satisfies the following condition: as obtained by FT-IR / ATR, the S / N ratio of the peaks on the surface of the copper component corresponding to the substances from the resin substrate is within a wavelength range of 700 cm⁻¹. -1 -4000cm -1 The content of metals on the surface of the resin substrate is less than 10; the total metal content / (C+O) composition ratio obtained by EDS elemental analysis is more than 0.4; the thickness of the seed layer is more than 0.1 μm and less than 2.0 μm.
[0086] Another embodiment of the present invention is a selection method, wherein the selection method is a method for selecting a copper component having a copper oxide layer formed on at least a portion of its surface, comprising: a step of peeling the copper component from a resin substrate after hot-pressing it to the resin substrate; a step of performing X-ray photoelectron spectroscopy (XPS) survey spectrum analysis on the surface of the copper component peeled from the resin substrate; a step of performing EDS elemental analysis on the surface of the resin substrate from which the copper component has been peeled; a step of measuring the thickness of a seed layer formed in the resin substrate from which the copper component has been peeled; and a step of selecting the copper component, wherein the copper component satisfies the following conditions: metal atoms contained in the copper oxide layer are detected on the surface of the resin substrate from which the copper component has been peeled; the composition ratio of the total metal / (C+O) of the resin substrate surface is 0.4 or more, as determined by EDS elemental analysis; and the thickness of the seed layer is 0.1 μm or more and 2.0 μm or less.
[0087] Each process can be performed according to the detailed instructions in the laminate manufacturing method. This selection method allows for the selection of copper components with good plating and wiring properties during circuit formation. Example
[0088] [1] Manufacturing of composite copper foil Examples 1-6 and Comparative Examples 2-3 used the smooth surface (glossy surface, flat surface compared to the opposite surface) of copper foil (DR-WS, thickness: 18μm) manufactured by Furukawa Electric Industries, Ltd. Comparative Example 4 used the rough surface of copper foil (FV-WS, thickness: 18μm) manufactured by Furukawa Electric Industries, Ltd., as a test piece in its untreated state. Comparative Examples 5-6 used the smooth surface (glossy surface, flat surface compared to the opposite surface) of copper foil (DR-WS, thickness: 18μm) manufactured by Furukawa Electric Industries, Ltd. Comparative Example 7 directly used ultra-thin copper foil with a carrier (MT18FL, ultra-thin copper foil thickness: 1.5μm) manufactured by Mitsui Metals & Minerals Co., Ltd. Additionally, as described below, Comparative Example 1 did not use composite copper foil.
[0089] (1) Pretreatment First, immerse the copper foil in the solution described below at 25°C for 1 minute. That is, the following method is used: Examples 1 and 2 consist of 2.5 g / L potassium carbonate and 1 vol% KBE-903 (3-aminopropyltriethoxysilane; manufactured by Shin-Etsu Silicon Co., Ltd.). Example 3 uses 2.5 g / L potassium carbonate and 0.06 g / L potassium bicarbonate; Examples 4-6 used potassium hydroxide at a concentration of 5 g / L; Comparative Example 2 is a solution of potassium carbonate at a concentration of 2.5 g / L; Comparative Example 3 consisted of a solution of potassium carbonate at 2.5 g / L and potassium bicarbonate at 0.06 g / L. Comparative Example 5 consisted of 5 g / L potassium hydroxide and 5 vol% KBM-603 (N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, manufactured by Shin-Etsu Silicon). Comparative Example 6 contained 5 g / L potassium hydroxide and 1 wt% BTA (benzotriazole).
[0090] (2) Oxidation treatment The pretreated copper foil is immersed in an oxidizing agent for oxidation treatment. In Examples 1, 2, 2, 5, and 6, a solution of sodium chlorite 58.3 g / L, potassium hydroxide 20 g / L, and potassium carbonate 39.1 g / L was used as the oxidant. Examples 3-6 used a solution of sodium chlorite 45 g / L, potassium hydroxide 12 g / L, and KBM-403 (3-glycidyl etheroxypropyltrimethoxysilane, manufactured by Shin-Etsu Silicon Co., Ltd.) 2 g / L as an oxidant. Comparative Example 3 used a solution of sodium chlorite 58.8 g / L, potassium hydroxide 8.8 g / L, potassium carbonate 3 g / L, and KBM-403 (3-glycidyl etheroxypropyltrimethoxysilane, manufactured by Shin-Etsu Silicon Co., Ltd.) 2 g / L as an oxidant. Examples 1, 2, 5, and 6 were immersed in an oxidizing agent at 73°C for 6 minutes, while Examples 3-6, 2, and 3 were immersed in an oxidizing agent at 73°C for 2 minutes.
[0091] (3) Pretreatment before plating After oxidation treatment, Examples 4-6 are performed using solvents for pre-plating treatment as follows. Example 4: A solution of 45 g / L tin(II) dihydrate and 1 mL / L hydrochloric acid was used to treat the sample at 45°C for 10 seconds. Example 5 uses a solution of 45 g / L ammonium chloride and treats the sample at 45°C for 60 seconds. Example 6 uses a 45 mL / L solution of 50% citric acid and treats it at 45°C for 60 seconds.
[0092] (4) Electroplating treatment After oxidation treatment, Examples 2, 3, and Comparative Example 3 were electroplated using a first Ni plating solution (240 g / L nickel sulfate, 45 g / L nickel chloride, and 20 g / L sodium citrate). Examples 4-6 were electroplated using a second Ni plating solution (240 g / L nickel sulfate and 20 g / L sodium citrate) after pre-plating treatment. Example 3 was immersed in the Ni plating solution for 1 minute before plating. Example 2 was plated at 50°C with a current density of 0.5 A / dm³. 2 ×116 seconds (=58C / dm) 2 The copper foil area was electroplated. Examples 3-6 and Comparative Example 3 were electroplated at 50°C with a current density of 0.5 A / dm². 2 ×45 seconds (=22.5C / dm) 2 Electroplating is performed on the copper foil area.
[0093] For both the examples and comparative examples, multiple test pieces were prepared under the same conditions described above. Table 1 summarizes these conditions. [Table 1]
[0094] <2. Pressing and peeling of resin substrates> (1) Method For the test pieces of Examples 1-6 and Comparative Examples 2-7, as prepregs, resin substrate peel tests were conducted using R5670KJ (manufactured by Panasonic), R5680J (manufactured by Panasonic), CT-Z (manufactured by Clare), NX9255 (manufactured by Park Electrochem), and R1551GG (manufactured by Panasonic).
[0095] First, the test piece prepreg was hot-pressed in a vacuum using a vacuum high-pressure press to obtain the laminated sample. Alternatively, with resin substrate R5670KJ (manufactured by Panasonic), hot pressing was performed at 0.49 MPa while heating to 110°C, followed by increasing the temperature and pressure and holding at 2.94 MPa and 210°C for 120 minutes. With resin substrate R5680J (manufactured by Panasonic), hot pressing was performed at 0.5 MPa while heating to 110°C, followed by increasing the temperature and pressure and holding at 3.5 MPa and 195°C for 75 minutes. When the resin substrate is NX9255 (manufactured by Park Electrochem), hot pressing is performed by heating to 260°C under pressure at 0.69 MPa, increasing the pressure to 1.5 MPa, heating to 385°C, and holding at 385°C for 10 minutes. When the resin substrate is R1551GG (manufactured by Panasonic), hot pressing is performed by heating to 100°C under pressure at 1 MPa, holding at that temperature for 10 minutes, then further heating to 180°C under pressure at 3.3 MPa, and holding at that temperature for 50 minutes. When the resin substrate is CT-Z (manufactured by Kurare), hot pressing is performed by heating to 260°C under pressure at 0 MPa, holding at 15 minutes, then further heating under pressure at 4 MPa, and holding at 300°C for 10 minutes. For these laminate samples, the copper components were peeled from the resin substrate according to a 90° peel test (Japanese Industrial Standard (JIS) C5016) (Figure 1). Visual observation results are shown below. Figure 2-1 Additionally, photographs of the surfaces of the resin side and copper foil side after peeling are shown for representative combinations. Figure 2-2 .
[0096] According to Figure 2, in the examples and comparative examples 5-6, it can be easily observed that the surface of the copper foil shifts towards the resin side; in contrast, in comparative examples 2-4, the surface of the copper foil does not shift towards the resin side. To prove that it is a substance, the following surface analysis was performed.
[0097] <3. Surface analysis of the resin substrate after peeling> Elemental analysis was performed on the surface of the peeled resin substrate. Specifically, the obtained resin substrate was analyzed using a Quantera SXM (manufactured by ULVAC-PHI) under the following conditions. As a negative control, an untreated resin substrate (R5670KJ; MEGTRON6) was analyzed (Comparative Example 1). (1) Survey spectrum First, elements are detected under the following conditions. X-ray source: Monochromatic Al Kα (1486.6 eV) X-ray beam diameter: 100μm (25w 15kV) Energy: 280eV, 1eV increments Point analysis: φ100μm Total number of times: 8
[0098] The results are shown in Table 2 and Figure 3. In the examples and Comparative Examples 5-6, the spectral peak intensity of Cu2p3 from the transferred copper atoms was greater than that of C1s caused by the resin substrate; in contrast, no Cu2p3 spectral peak was detected in Comparative Examples 1-4, or its intensity was less than that of C1s. This indicates that in the comparative examples, copper atoms were hardly transferred to the resin substrate, or were almost absent from the surface portion of the resin substrate that could be detected by XPS.
[0099] In Example 1, since the copper foil was not plated, only Cu atoms were transferred and detected on the resin substrate side. In Examples 2 and 3, due to Ni plating, both Cu and Ni atoms were transferred and detected on the resin side.
[0100] Furthermore, compared to Comparative Examples 1-4, the proportion of C1s in Examples 5-6 was smaller. It is believed that in these examples, the transfer of copper oxide or cuprous oxide resulted in a relatively smaller proportion of C1s on the surface. [Table 2]
[0101] <4. Determination of Ra and surface area of composite copper foil before and after hot pressing> (1) Method For the composite copper foil test pieces of Examples 1-6 and Comparative Examples 2-6, the surface area before and after hot pressing was calculated using an OPTELICS H1200 confocal microscope (manufactured by Lasertech Co., Ltd.). As for the measurement conditions, the mode was confocal, the scanning area was 100 μm × 100 μm, the light source was Blue, and the cutoff value was 1 / 5. The objective lens was set to ×100, the contact lens to ×14, the digital zoom to ×1, and the Z-spacing to 10 nm. Data was obtained at three locations, and the surface area is the average of the three locations.
[0102] (2) Results As shown in Table 3, Ra and surface area decreased in Examples 5 and 6 before hot pressing and after peeling; in contrast, they increased in Comparative Examples 2 and 4. This indicates that in the Examples, all or part of the protrusions of the composite copper foil shifted towards the resin side; in contrast, in Comparative Examples 2 and 4, a portion of the resin shifted towards the composite copper foil. [Table 3]
[0103] <5. ΔE of copper foil before hot pressing and after peeling * Calculation of ab> (1) Method The color difference (L) on the surface of each composite copper foil test piece before hot pressing and after peeling was measured. * a * b * ), calculate ΔE according to the obtained value using the following formula. * ab. ΔE * ab=[(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 ] 1 / 2
[0104] (2) Results As shown in Table 4, before and after hot pressing, ΔE*ab was 15 or more in Examples and Comparative Examples 5-6; in contrast, it was less than 15 in Comparative Examples 2-4. This is because, in Examples and Comparative Examples 5-6, the metal contained in the copper oxide layer transferred to the resin substrate, resulting in a greater color change in the copper component; while in Comparative Examples 2-4, the copper oxide layer remained directly on the copper component, resulting in a smaller color change in the copper component. Therefore, the more metal contained in the copper oxide layer is transferred, the greater the difference becomes. In fact, this is also reflected in the photographs in Figure 2; after peeling, the resin side showed greater coloration in Examples and Comparative Examples 5-6, while the resin side was almost white in Comparative Examples 2-4. [Table 4]
[0105] <6. Analysis of the surface of the transferred composite copper foil based on attenuated total internal reflection absorption Fourier transform infrared spectroscopy (FT-IR / ATR method)> (1) Method As the resin substrate, R1551GG (epoxy), R5670KJ, R5680J (PPE), NX9255 (PTFE), or CT-Z (LCP) were used for hot pressing. The peeled composite copper foil test pieces were analyzed by FT-IR / ATR under the following test conditions. Measurement conditions Parkin Elmer manufactured Spectrum 100 ATR method Crystal: Germanium Resolution: 4 Number of scans: 4 Pressure (force gauge): 40±5 [N] Spectral display: absorbance
[0106] (2) Calculation of S / N (signal / noise) ratio Under the same conditions as during hot-pressing of composite copper foil, only the resin substrate was heated and pressurized. FT-IR measurements were then performed on the resin substrate at 50 cm⁻¹. -1 Any wavelength within the range that does not contain peaks from the resin is selected. In this embodiment, 3800 cm⁻¹ -1 -3850cm -1 The wavelength at which there is no peak from the resin. Furthermore, it was confirmed that the wavelength range of 700cm... -1 -4000cm -1 The wavelength of the maximum peak was detected. When R1551GG was used as the resin substrate, the wavelength was 1200 cm⁻¹. -1 The wavelength near which the maximum peak was detected was 1190 cm⁻¹ when using R5670KJ and R5680J. -1 The wavelength near which the maximum peak was detected was 1232 cm⁻¹ when using the NX9255. -1 The wavelength near which the maximum peak was detected was 1741 cm⁻¹. -1 The wavelength near which the maximum peak was detected is shown in Figure 4- Figure 8 The arrow indicates the wavelength at which the maximum peak was detected.
[0107] The surface of the transferred copper component was measured by FT-IR. For the wavelength at which the maximum peak was detected, a baseline was drawn connecting the poles at both ends of the peak with a straight line. The difference between the baseline and the maximum height of the peak was taken as the signal value (S). At a wavelength of 3800 cm⁻¹... -1 -3850cm -1 At the point, the difference between the maximum and minimum values of the detected peak is taken as the noise value (N), and the S / N ratio is calculated.
[0108] (3) Results The results are shown in Figure 4- Figure 8 As shown in Table 5. [Table 5]
[0109] As shown in Table 5, in Examples 5 and Comparative Examples 6, no peaks with an S / N ratio of 10 or higher corresponding to organic matter from the resin were detected on the composite copper foil side; in Comparative Examples 2 and 4, peaks with an S / N ratio of 10 or higher corresponding to organic matter from the resin were detected on the composite copper foil side.
[0110] This is because, in Comparative Examples 2-4, the metal on the surface of the composite copper foil hardly transferred, and when the composite copper foil was peeled from the resin substrate, resin agglomeration and destruction occurred, and the destroyed resin adhered to the surface of the composite copper foil, thus a peak corresponding to organic matter from the resin was detected. On the other hand, in the Examples and Comparative Examples 5-6, since the metal on the surface of the composite copper foil transferred to the resin substrate, almost no resin adhered to the composite copper foil after it was peeled from the resin substrate, and no peak with an S / N ratio of 10 or more corresponding to organic matter from the resin was detected.
[0111] That is, in Comparative Examples 2-4, since the adhesion strength between the copper oxide layer and the copper component is greater than the adhesion strength between the copper oxide layer and the resin substrate, the metal on the surface of the composite copper foil does not transfer, resulting in resin coagulation and destruction. On the other hand, in the Examples and Comparative Examples 5-6, since the adhesion strength between the copper oxide layer and the copper component is less than the adhesion strength between the copper oxide layer and the resin substrate, the metal on the surface of the composite copper foil transfers, resulting in almost no resin adhesion.
[0112] [2] Analysis of resin surface and seed layer The composite copper foil prepared in [1] was hot-pressed onto a resin substrate and then peeled off from the resin substrate. The surface and seed layer of the resin substrate were analyzed. The resin substrate was an R5670KJ (manufactured by Panasonic). The hot-pressing was performed by heating to 110°C under a pressure of 0.49 MPa. The temperature and pressure were then increased, and the hot-pressing was performed by holding the foil at 210°C and 2.94 MPa for 120 minutes.
[0113] <1. Elemental Analysis using EDS (Energy Dispersive X-ray Spectrometer)> First, elemental analysis was performed using an EDS (Energy Dispersive X-ray Spectrometer) (manufactured by Oxford, trade name: X-Max Extreme) (conditions: accelerating voltage 10 kV, magnification 30,000x). Figure 9 Representative secondary electron images and EDS elemental mappings of Cu are shown; Tables 6 (Examples) and 7 (Comparative Examples) show the ratios (sum of the proportions of the metal elements / (sum of the proportions of C and O)) calculated based on the proportions (atom%) of each element (C, O, Ni, Cu, Sn).
[0114] In the embodiments, when the proportion of Cu is 10 atom% or more, Cu is transferred at a high proportion, and a ratio of (sum of metal element proportions / (sum of C and O proportions)) of 0.4 or more is obtained, resulting in good plating formability. On the other hand, in Comparative Examples 2 and 3, the proportion of Cu is 0.1 atom% or less, Cu is hardly transferred, and plating formability is poor. Furthermore, in Comparative Examples 5 and 6, the ratio of (sum of metal element proportions / (sum of C and O proportions)) becomes lower than 0.4, and these also result in poor plating formability.
[0115] Thus, the resin with a seed layer manufactured using the composite copper foil of the embodiment exhibits good plating formation properties from the viewpoint of surface element composition.
[0116] <2. Thickness of the seed layer> Next, the thickness of the seed layer was measured. Specifically, in the cross-section of an SEM (10,000x magnification), for the layer in which the copper protrusion is embedded in the resin substrate, the maximum gap was investigated between two parallel straight lines that contact the top edge (corresponding to the top of the layer) and the bottom edge (corresponding to the bottom of the layer), and this gap was taken as the thickness of the seed layer. Figure 10 Representative SEM images are shown, and thickness measurement results are presented in Tables 6 and 7.
[0117] In the embodiments, the seed layer thickness is as thin as 0.36 μm-1.70 μm, thus resulting in good wiring formation. On the other hand, in Comparative Examples 2 and 3, the seed layer thickness is 0 μm, and since no metal transfer occurs, almost no plating is formed. In Comparative Example 7, the seed layer is too thick, making it difficult to miniaturize the circuit, as described below. <3> As shown, the wiring formation is also poor.
[0118] Thus, the resin with a seed layer manufactured using the composite copper foil of the embodiment exhibits good wiring formation properties in terms of the thickness of the seed layer.
[0119] <3. Plating Formation> (1) For the resin having the seed layer of Examples 1-6 and Comparative Examples 2-7, chemical plating was performed as follows, followed by plating treatment to form a second seed layer.
[0120] First, pretreatment was performed at 25°C for 1 minute with a 100 mL / L HCl solution. Then, treatment was carried out at 30°C for 5 minutes with a 250 mL / L HCl solution containing catalyst OPC-80 Catalyst M (manufactured by Okuno Pharmaceutical), followed by rinsing with water and activation treatment. After further rinsing with water, treatment was carried out at 80°C for 10 minutes with chemical copper plating solution OPC-700 (manufactured by Okuno Pharmaceutical), followed by rinsing with water.
[0121] Next, a commercially available photosensitive dry film is applied, exposed through a mask, and developed using 0.8% sodium bicarbonate to form a plating resist. Then, a commercially available copper plating solution is used, applied at a current density of 1 A / dm³. 2 Electroplating of copper was carried out at 30°C for 30 minutes, thereby forming an electroplated copper film with a thickness of 15μm.
[0122] Furthermore, after removing the plating resist by stripping with 5% potassium hydroxide, the seed layer under the plating resist is dissolved and removed by etching with a mixture of sulfuric acid and hydrogen peroxide to obtain a laminated wiring circuit board. (2) The resin having the seed layer of Example 3 is subjected to electroplating treatment only to form a second seed layer. Specifically, a commercially available copper plating solution is used at a current density of 1 A / dm³. 2 An electroplated copper film is formed at 30℃.
[0123] (3) After forming the copper plating film, attach the cerodeta (registered trademark) (manufactured by Nichiban), peel off the cerodeta (registered trademark), and analyze the SEM cross-sectional image (30,000x). If a plating of 0.1μm or larger is formed, it is 0; otherwise, it is ×. Figure 11 SEM cross-sectional images (30,000x) of Examples 1, 2, 3 and Comparative Example 7 are shown.
[0124] <4. Wiring Formation> For resins with a seed layer, a commercially available photosensitive dry film is applied to the formed seed layer, exposed through a mask, and developed with 0.8% sodium bicarbonate to form a coating resist.
[0125] Then, using a commercially available copper plating solution, at a current density of 1 A / dm 2 Electroplating of copper was carried out at 30℃ for 30 minutes to form a copper film with a thickness of 15μm.
[0126] Furthermore, after removing the plating resist by stripping with 5% potassium hydroxide, the seed layer under the plating resist is dissolved and removed by etching with a mixture of sulfuric acid and hydrogen peroxide to obtain a laminated wiring circuit board.
[0127] The etching factor was calculated using the following formula based on the SEM cross-sectional image of the test piece. The results are shown in Tables 6 and 7. Etching Factor (EF) Calculation Formula
[0128] The smaller the etch factor, the greater the width difference between the upper and lower sides of the trapezoidal wiring, and the more extreme the trapezoid. If the width of the bottom side is shortened for miniaturization, the width of the top side cannot be guaranteed, so it is not suitable for miniaturization.
[0129] According to Tables 6 and 7, Comparative Examples 2, 3, 5, and 6 could not form wiring, while Comparative Example 7 had a low etch factor and poor wiring formation. [Table 6][Table 7]
Claims
1. A copper component, wherein, The copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed. When the copper component is peeled off from the resin substrate after being hot-pressed onto it... The signal-to-noise ratio (S / N) of the peaks on the surface of the copper component corresponding to the material from the resin substrate was obtained by attenuated total reflectance absorption Fourier transform infrared spectroscopy (FT-IR / ATR method) in the wavelength range of 700 cm⁻¹. -1 -4000cm -1 Below 10 EDS elemental analysis revealed that the total metal content / (C+O) ratio on the surface of the resin substrate was greater than 0.
4. The thickness of the seed layer formed in the resin substrate is 0.1 μm or more and 2.0 μm or less.
2. The copper component as claimed in claim 1, wherein, The S / N ratio of the peak is below 7.
3. A copper component, wherein, The copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed. When the copper component is peeled off from the resin substrate after being hot-pressed onto it... X-ray photoelectron spectroscopy (XPS) survey spectrum analysis detected metal atoms contained in the copper oxide layer on the surface of the resin substrate after the copper component was removed. EDS elemental analysis revealed that the total metal content / (C+O) ratio on the surface of the resin substrate was greater than 0.
4. The thickness of the seed layer formed in the resin substrate is 0.1 μm or more and 2.0 μm or less.
4. The copper component as described in claim 3, wherein, The sum of the main peak intensities of the metal elements detected from the surface of the resin substrate from which the copper component has been stripped is greater than the peak intensity of C1s.
5. The copper component as claimed in claim 4, wherein, On the surface of the resin substrate from which the copper component has been removed, the ratio of [total surface atomic percentage of metal elements (atom%)] / [surface atomic percentage of C1s (atom%)] calculated based on XPS measurements is 0.010 or higher.
6. The copper component as claimed in claim 4, wherein, The combined percentage of surface atomic composition of Cu2p3 and Ni2p3 detected by the Survey spectrum analysis was greater than 1.5 atom%.
7. The copper component as claimed in claim 4, wherein, The surface atomic composition percentage of Cu2p3 detected by the Survey spectrum analysis is above 1.0 atom%.
8. The copper component as claimed in any one of claims 1-7, wherein, The surface on which the layer containing the copper oxide is formed has a Ra of 0.04 μm or more, and the Ra of the surface of the copper component peeled off from the resin substrate is less than 100% relative to the above Ra.
9. The copper component as claimed in any one of claims 1-7, wherein, The surface area of the copper component peeled off from the resin substrate is less than 100% relative to the surface area of the surface on which the layer containing the copper oxide is formed.
10. The copper component as claimed in any one of claims 1-7, wherein, The color difference (ΔE*ab) between the surface on which the layer containing the copper oxide is formed and the surface of the copper component peeled off from the resin substrate is 15 or more.
11. The copper component as claimed in any one of claims 1-7, wherein, The resin substrate contains at least one insulating resin selected from the group consisting of polyphenylene oxide (PPE), epoxy resin, polyoxymethylene (PPO), polybenzoxazole (PBO), polytetrafluoroethylene (PTFE), liquid crystal polymer (LCP), or thermoplastic polyimide (TPI), fluororesin, polyetherimide, polyetheretherketone, polycyclic olefin, bismaleimide resin, low dielectric constant polyimide, and cyanate ester resin.
12. The copper component as claimed in any one of claims 1-7, wherein, The copper component is hot-pressed onto the resin substrate under conditions of 50℃-400℃ temperature, 0MPa-20MPa pressure, and 1 minute-5 hours.
13. The copper component as claimed in any one of claims 1-7, wherein, The layer containing the copper oxide contains a metal other than copper.
14. The copper component as claimed in claim 13, wherein, The metal other than copper is Ni.
15. A selection method, wherein, The selection method is a method for selecting copper components, wherein the copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed, and the selection method includes: The process of hot-pressing the copper component to the resin substrate and then peeling it off from the resin substrate; The process of analyzing the surface of the copper component peeled from the resin substrate by attenuated total reflectance absorption Fourier transform infrared spectroscopy (FT-IR / ATR method). A process of performing EDS elemental analysis on the surface of the resin substrate from which the copper component has been removed; The process of measuring the thickness of the seed layer formed in the resin substrate after the copper component has been peeled off; and The process of selecting copper components The copper component satisfies the following condition: as obtained by the FT-IR / ATR method, the S / N ratio of the peak corresponding to the substance from the resin substrate on the surface of the copper component is within the wavelength range of 700 cm⁻¹. -1 -4000cm -1 The content of metals on the surface of the resin substrate is 10 or less; the composition ratio of total metals / (C+O) on the surface of the resin substrate is 0.4 or more, as obtained by EDS elemental analysis; the thickness of the seed layer is 0.1 μm or more and 2.0 μm or less.
16. A selection method, wherein, The selection method is a method for selecting copper components, wherein the copper component is a copper component on which at least a portion of its surface has a layer containing copper oxide formed, and the selection method includes: The process of hot-pressing the copper component to the resin substrate and then peeling it off from the resin substrate; The process of performing X-ray photoelectron spectroscopy (XPS) survey spectrum analysis on the surface of the copper component peeled from the resin substrate; A process of performing EDS elemental analysis on the surface of the resin substrate from which the copper component has been removed; The process of measuring the thickness of the seed layer formed in the resin substrate after the copper component has been peeled off; and The process of selecting copper components The copper component satisfies the following conditions: metal atoms contained in the layer containing the copper oxide are detected on the surface of the resin substrate from which the copper component has been removed; the composition ratio of the total metal / (C+O) on the surface of the resin substrate is 0.4 or more, as determined by the EDS elemental analysis; and the thickness of the seed layer is 0.1 μm or more and 2.0 μm or less.
17. The selection method as described in claim 16, wherein, The selection method further includes: The process of locally coating the surface of the copper component with a silane coupling agent or rust inhibitor; and The process of forming a layer containing the copper oxide by oxidizing the partially coated surface.
18. The selection method as described in claim 17, wherein, The surface of the copper component is oxidized using an oxidizing agent.
19. The selection method as described in claim 17 or 18, wherein, The silane coupling agent is selected from the group consisting of silane, tetraorganosilane, aminoethyl-aminopropyltrimethoxysilane, (3-aminopropyl)trimethoxysilane, (1-[3-(trimethoxysilyl)propyl]urea), (3-aminopropyl)triethoxysilane, (3-chloropropyl)trimethoxysilane, (3-glycidyl ether oxypropyl)trimethoxysilane, dimethyl dichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, triethoxy(isobutyl)silane, triethoxy(octyl)silane, tri(2-methoxyethoxy)(vinyl)silane, trichlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, trichlorotriethoxysilane, and ethylene-trimethoxysilane.
20. The selection method as described in claim 17 or 18, wherein, The rust inhibitor is selected from 1H-tetrazole, 5-methyl-1H-tetrazole, 5-amino-1H-tetrazole, 5-phenyl-1H-tetrazole, 1,2,3-triazole, 1,2,4-triazole, 1,2,3-benzotriazole, 5-methyl-1H-benzotriazole, 5-amino-1H-benzotriazole, 2-mercaptobenzothiazole, 1,3-dimethyl-5-pyrazolone, pyrrole, 3-methylpyrrole, 2,4-dimethylbenzothiazole, etc. The group consisting of methylpyrrole, 2-ethylpyrrole, pyrazole, 3-aminopyrazole, 4-methylpyrazole, 3-amino-5-hydroxypyrazole, thiazole, 2-aminothiazole, 2-methylthiazole, 2-amino-5-methylthiazole, 2-ethylthiazole, benzothiazole, imidazole, 2-methylimidazolium, 2-ethylimidazolium, 2-butylimidazolium, 5-aminoimidazolium, 6-aminoimidazolium, benzimidazole, and 2-(methylthio)benzimidazole.
21. The selection method as described in claim 17 or 18, wherein, The selection method further includes the following step: forming a layer containing a metal other than copper on the surface that has undergone the oxidation treatment.
22. The selection method as described in claim 21, wherein, The metal other than copper is Ni.
23. The selection method as described in claim 16, wherein, The selection method further includes: The process of oxidizing the surface of the copper component; and The process of treating the surface that has undergone the oxidation treatment with a solvent to form a layer containing the copper oxide.
24. The selection method as described in claim 23, wherein, The surface of the copper component is oxidized using an oxidizing agent.
25. The selection method as described in claim 23, wherein, The solvent is selected from the group consisting of nickel chloride, zinc chloride, ferric chloride, chromium chloride, ammonium citrate, potassium chloride, ammonium sulfate, ammonium chloride, nickel ammonium sulfate, tin(II) chloride and citric acid.
26. The selection method as described in any one of claims 23-25, wherein, The selection method further includes the following step: forming a layer containing a metal other than copper on the surface treated with the solvent.
27. The selection method as described in claim 26, wherein, The metal other than copper is Ni.
28. A method for manufacturing a copper component, wherein, The manufacturing method is a method for manufacturing the copper component according to any one of claims 1-14, the manufacturing method comprising: 1) A process of locally coating the surface of a copper component with a silane coupling agent or a rust inhibitor; and 2) The process of forming a layer containing the copper oxide by oxidizing the partially coated surface.
29. A method for manufacturing a copper component, wherein, The manufacturing method is the manufacturing method of the copper component according to claim 13 or 14, the manufacturing method comprising: 1) A process of locally coating the surface of a copper component with a silane coupling agent or a rust inhibitor; 2) The process of forming a layer containing the copper oxide by oxidizing the partially coated surface; and 3) The process of forming a layer containing a metal other than copper on the surface that has undergone oxidation treatment.
30. The method for manufacturing a copper component as described in claim 29, wherein, The metal other than copper is Ni.
31. A method for manufacturing a copper component, wherein, The manufacturing method is a method for manufacturing the copper component according to any one of claims 1-14, the manufacturing method comprising: 1) A process of locally coating the surface of a copper component with a silane coupling agent or a rust inhibitor; 2) The process of forming a layer containing the copper oxide by oxidizing the partially coated surface; and 3) The step of treating the surface that has undergone the oxidation treatment with a solvent.
32. The method for manufacturing a copper component as described in claim 31, wherein, The solvent contains a compound selected from the group consisting of nickel chloride, zinc chloride, ferric chloride, chromium chloride, ammonium citrate, potassium chloride, ammonium sulfate, ammonium chloride, nickel ammonium sulfate, tin(II) chloride, and citric acid.
33. A method for manufacturing a copper component, wherein, The manufacturing method is the manufacturing method of the copper component according to claim 13 or 14, the manufacturing method comprising: 1) A process of forming a layer containing the copper oxide by oxidizing the surface of the copper component; 2) The step of treating the surface that has undergone the oxidation treatment with a solvent; and 3) The process of forming a layer containing a metal other than copper on the surface treated with the solvent. The solvent contains components that dissolve the copper oxide.
34. The method for manufacturing a copper component as described in claim 33, wherein, The solvent contains a compound selected from the group consisting of nickel chloride, zinc chloride, ferric chloride, chromium chloride, ammonium citrate, potassium chloride, ammonium sulfate, ammonium chloride, nickel ammonium sulfate, tin(II) chloride, and citric acid.
35. The method for manufacturing a copper component as described in claim 34, wherein, The metal other than copper is Ni.
Citation Information
Patent Citations
Copper foil for electronic circuit and method for forming electronic circuit
JP2002176242A
Composite multilayer substrate
JP2005223226A
Printed wiring board and manufacturing method thereof
JP2010267891A
Automatic circuit board testing system and testing method thereof
JP2021071460A
Composite copper components
JP6806405B1
